Multimethod Research, Causal Mechanisms, and Case Studies : An Integrated Approach - Goertz, Gary, 1953- (Book collections on Project MUSE., 2017)
"An innovative and accessible textbook on multimethod and case-study research. Multimethod research has become indispensable to doing social science, and is essential to anyone who conducts large-scale research projects in political science, sociology, education, comparative law, or business. This authoritative and accessible book offers the first truly comprehensive approach to multimethod and case-study research, and is particularly aimed at students of qualitative methods in the social sciences. Walking step-by-step through these cutting-edge tools and techniques, Gary Goertz introduces a new integrated approach that unites three corners of a powerful research triad--causal mechanisms, cross-case causal inference, and within-case causal inference. He explains how the investigation of causal mechanisms and the making of within-case causal inference are the central goals of multimethod and case study research, and provides a logic for connecting case studies and causal mechanism analysis with cross-case analysis, whether they are statistical analyses, experiments, or QCA. In addition, Goertz analyzes how one can generalize using case studies, as well as systematically test game-theoretic and other models using multiple case studies. Provides a fully integrated approach to multimethod and case-study research An essential resource for students and researchers in political science, sociology, education, law, and business Covers constraint causal mechanism, game theory and case studies, QCA, and the use of case studies to systematically test and generalize theories An ideal textbook for a first-year graduate course in methods or research design "--